Cost‐effectiveness analysis of sofosbuvir plus peginterferon/ribavirin in the treatment of chronic hepatitis C virus genotype 1 infection. Issue 6 (28th July 2014) - Saab, S.; Gordon, S. C.; Park, H.; Sulkowski, M.; Ahmed, A.; Younossi, Z.
Summary Background Sofosbuvir, an oral NS5B nucleotide polymerase inhibitor, is indicated for the treatment of patients infected with hepatitis C virus (HCV). Aim To evaluate the long‐term health economic outcomes of sofosbuvir + pegylated interferon alfa/ribavirin (pegIFN/RBV) compared with current treatments in patients infected with HCV genotype 1 in the US. Methods A decision‐analytic Markov model was developed to estimate health outcomes, number needed to treat and short‐term and long‐term economic outcomes, including incremental cost‐effectiveness ratios and cost per sustained virological response (SVR), for several sofosbuvir–comparator regimen pairings for a cohort of 10 000 patients. It considered three patient cohorts: treatment‐naïve, treatment‐experienced and treatment‐naïve human immunodeficiency virus (HIV) co‐infected. Subgroup analyses were conducted for treatment‐naïve patients with and without cirrhosis. Results Reductions in the incidence of new cases of liver‐disease complications with sofosbuvir + pegIFN/RBV compared with pegIFN/RBV, boceprevir + pegIFN/RBV, telaprevir + pegIFN/RBV and simeprevir + pegIFN/RBV were 64–82%, 50–68%, 43–58% and 33–56%, respectively. Sofosbuvir + pegIFN/RBV was typically associated with the lowest 1‐year cost per SVR. When considering the lifetime incremental cost per quality‐adjusted life‐year gained, sofosbuvir + pegIFN/RBV was the most cost‐effective treatment option assessed. Sofosbuvir + pegIFN/RBV generally dominated (less costly and more effective than) boceprevir + pegIFN/RBV, telaprevir + pegIFN/RBV and simeprevir + pegIFN/RBV. Conclusion Sofosbuvir + pegIFN/RBV yields more favourable future health and economic outcomes than current treatment regimens for patients across all levels of treatment experience and cirrhosis stage, as well as for individuals with or without HIV co‐infection.